Beginning of the Pandemic: COVID-19-Elicited Anxiety as a Predictor of Working Memory Performance - Fellman, Daniel; Ritakallio, Liisa; Waris, Otto; Jylkkä, Jussi; Laine, Matti (Frontiers in Psychology, 2020)
Increasing evidence indicates that the COVID-19 pandemic is associated with adverse psychological effects, including heightened levels of anxiety. This study examined whether COVID-19 related anxiety levels during the early stage of the pandemic predicted demanding working memory (WM) updating performance. Altogether 201 healthy adults (age range 18-50) mostly from North America and the British Isles were recruited to this WM study via the crowdsourcing site www.prolific.co. The results showed that higher levels of COVID-19-related anxiety during the first weeks of the pandemic outbreak were associated with poorer WM updating performance. Critically, the unique role of COVID-19 related anxiety on WM could not be explained by demographic factors or other psychological factors, such as state and trait anxiety, or fluid intelligence. Moreover, across three assessment points over 5-6 weeks, COVID-19-related anxiety levels tended to decrease over time. This pattern of results may reflect an initial psychological “shock wave” of the pandemic, the cognitive effects of which may linger for some time albeit the initial anxiety associated with the pandemic would change with habituation and increasing information. Our results contribute to the understanding of cognitive-affective reactions to a major disaster.